Les urgences ORL pédiatriques au Centre Hospitalier Départemental du Borgou de Parakou, Bénin....... - HOUNKPATIN, Spéro; ADEDEMY, S.; AVAKOUDJO, FRANÇOIS; LAWSON ÉPSE AFOUDA, SONIA RUTH JOSÉPHINE; AGOSSOU, J.; KOUDAMADJO, A.; DOSSOU KPANOU, Karl; ADJIBABI, WASSI; VODOUHE, SOGBADJI JOSEPH (My University, 2012)
.....
Keywords: ORL; PEDIATRIE; URGENCES; BENIN